A Standard Study of the Role of the Tourism Sector in Achieving Economic Growth in Tunisia for the Period (1995-2017 - عبد القادر عبد الرحمان; عبد الكريم المؤمن; بن عودة حساني (Journal of Economics and Administrative Sciences, 2019)
This study examines the relationship between the increase in the number of tourists coming to Tunisia and GDP during the period 1995-2017, using the methodology of joint integration, causal testing and error correction model. The research found the time series instability of the logarithm of the number of tourists coming to Tunisia and the output logarithm but after applying the first differences, these chains become stable, THUS these time series are integrated in the first differences. Using the Johansson method, we found the possibility of a simultaneous integration relationship between the logarithm of the number of tourists coming to Tunisia and the logarithm of GDP in Tunisia, and there is a causal relationship in one direction between them. By estimating the error correction model, the actual deviation from the balance between the two variables was corrected by 18% each year.